Longitudinal Study Of Antecedents Of Work-Family And Family-Work Conflict - Zaiton, Hassan; Hana, Hamidi (Universiti Malaysia Sarawak, UNIMAS, 2014)
Although work-family conflict studies are available in Malaysia, most rely on crosssectional design and the focus is on women. This study is using longitudinal design on heterogeneous sample which is aimed to enhance the understanding of the antecedents of work-family and family-work conflict from work and family demands and resources. The respondents were 296 employees in diverse industries from six public and private organizations in Kuching, Sarawak. Two surveys were conducted at a three month interval. Structural Equation Modeling via AMOS 7.0 was used to analyze the data. The study found that the respondents reported higher work-family conflict than familywork conflict. Demands from work predicted work-family conflict positively while resources from work predicted work-family conflict (WFC) negatively. None resources and demands predicted family-work conflict (FWC). The findings implied the importance of organizations in influencing work-family balance of the employees.